Reaction of Highly Volatile Organic Compounds with Organolithium Species in Flow Microreactor - Muta, Kensuke; Okamoto, Kazuhiro; Nagaki, Aiichiro (Synlett, 2023)
Highly volatile organic compounds (VOCs) with boiling points (bp) around or below room temperature are generally difficult to manipulate precisely in liquid-phase organic reactions although they offer significant atom-economic advantages. We have developed a novel approach using a jacketed syringe pump to enable the formylation of organolithium species in a continuous-flow system under ambient pressure. Methyl formate (bp 32 °C) worked as a formylating agent and was successfully delivered to the continuous operation for over 30 minutes in our microflow system. This methodology was successfully expanded to the application of acetaldehyde (bp 21 °C) and heptafluoropropyl bromide (bp 12 °C).
Keywords: volatile organic compounds; organolithium species; flow chemistry; reactive intermediates; device control